2011
DOI: 10.1186/1471-2458-11-73
|View full text |Cite
|
Sign up to set email alerts
|

Variability in school closure decisions in response to 2009 H1N1: a qualitative systems improvement analysis

Abstract: BackgroundSchool closure was employed as a non-pharmaceutical intervention against pandemic 2009 H1N1, particularly during the first wave. More than 700 schools in the United States were closed. However, closure decisions reflected significant variation in rationales, decision triggers, and authority for closure. This variability presents the opportunity for improved efficiency and decision-making.MethodsWe identified media reports relating to school closure as a response to 2009 H1N1 by monitoring high-profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Though ordered for some schools in spring, summer, and fall of 2009, school-closures were determined typically by local school districts and individual schools; and closure durations rarely exceeded a few days [13,14]. It was reported that H1N1 school closure experience had much local variation in decision-making authority, disagreement between school administrators and public health officials, and lack of clarity about the goals for closure [15]. A review of laboratory-confirmed H1N1 cases in Alberta, Canada found that the 2009 summertime closure of schools had interrupted virus transmission among school-aged children but then failed to prevent a second wave of the pandemic when schools re-opened in the fall [16].…”
Section: Introductionmentioning
confidence: 99%
“…Though ordered for some schools in spring, summer, and fall of 2009, school-closures were determined typically by local school districts and individual schools; and closure durations rarely exceeded a few days [13,14]. It was reported that H1N1 school closure experience had much local variation in decision-making authority, disagreement between school administrators and public health officials, and lack of clarity about the goals for closure [15]. A review of laboratory-confirmed H1N1 cases in Alberta, Canada found that the 2009 summertime closure of schools had interrupted virus transmission among school-aged children but then failed to prevent a second wave of the pandemic when schools re-opened in the fall [16].…”
Section: Introductionmentioning
confidence: 99%
“…Certain public health departments reported difficulties in communicating the updated guidance on school closures to their communities, especially communities that were planning to implement school closures or had already done so ( 30 , 31 ).…”
mentioning
confidence: 99%
“…I think that in situations where the strength of recommendation—the data on which recommendation is based—is less strong, then more flexibility is appropriate” (interview 5). This idea was echoed by nearly every public health and public education official we interviewed, as well as in other studies on the use of school closure during the 2009 pandemic (Jackson et al 2013; Klaiman, Kraeme, and Stoto 2011; Jarquin et al 2011). …”
Section: Resultsmentioning
confidence: 83%